Penetapan Honorarium Notaris dalam Pembuatan Akta di Kota Pariaman - Raji Saputra; Azmi Fendri; Delfiyanti Delfiyanti (UNES Law Review, 2023)
The violation of the Code of Ethics that occurred in Pariman City was caused by the Notary's actions which were not in accordance with the Regulations on the Notary's Office and the Notary's Code of Ethics. Meanwhile, the violation of the Code of Ethics in Pariaman City was the determination of the Notary's Honorarium which was below the stipulated standards. determine the UUJN and the Notary's Code of Ethics, with this the Notary concerned has violated article 36 UUJN No. 2 of 2014 and the Notary's Code of Ethics in article 4 paragraph 10. Implementation of determining the Notary's honorarium in making deeds in the city of Pariaman. The honorarium received by Notaries in Pariaman was a violation of the Code of Ethics which violated Article 4 paragraph 10 of the 2015 Notary Code of Ethics. according to its authority. Up to Rp. 100,000,000.00 the maximum honorarium received is 2.5%, then above Rp. 100,000,000.00 - Rp. 1,000,000,000.00 one billion the maximum honorarium received is 1.5%, above Rp. 000,000,000.00 honorarium received is based on an agreement between the Notary and the parties, but does not exceed 1% according to the object for which the deed is made. The honorarium received by Notaries in Pariaman was a violation of the Code of Ethics which violated Article 4 paragraph 10 of the 2015 Notary Code of Ethics which resulted in the Notary concerned committing a violation, for several reasons, namely because the client was incapable and there was a mutually acquainted relationship between the client and the Notary concerned. Supervision by the Notary organization in determining the Notary's honorarium in connection with the making of deeds in the city of Pariaman. Supervision from the Indonesian Notary Association (I.N.I) on the behavior and actions of Notaries in Pariaman so that unhealthy competition does not arise through the determination of Notary Supervision to differentiate between the behavior and actions carried out by Notaries in carrying out their positions by the Supervisory Council.